Response to anaplastic lymphoma kinase inhibitor in gastric cancer harboring DCTN1–ALK fusion: a case report and review - Wang, Huadi; You, Liangkun; Pan, Hong; Qiu, Xiaotong; Sheng, Jin (Frontiers in Immunology, 2025)
Anaplastic lymphoma kinase (ALK) rearrangements are exceedingly rare in gastric cancer, and uncommon fusion types add to the difficulties of proper, precise treatment strategies. Although detected in non-small cell lung cancer (NSCLC), inflammatory myofibroblastic tumors (IMTs), and Spitz tumors, the DCTN1–ALK fusion has not previously been reported in gastric cancer. This report describes the first case of gastric adenocarcinoma harboring a DCTN1–ALK fusion that was successfully treated with the ALK-targeted agent alectinib after first- and second-line chemotherapy-based regimens had failed. Progression-free survival on alectinib was 11.5 months until KRAS amplification emerged on serial circulating tumor DNA analysis, leading to rapid systemic relapse. The other documented cases with DCTN1–ALK fusion treated with the first or second generation of ALK inhibitors indicated this rare fusion as an actionable driver gene mutation. This successful personalized anti-tumor strategy highlights the clinical utility of comprehensive genomic profiling and liquid biopsy in detecting and monitoring actionable ALK fusions in solid tumors.